1994
DOI: 10.1002/hep.1840190407
|View full text |Cite
|
Sign up to set email alerts
|

Immunological disorders in C virus chronic active hepatitis: A prospective case-control study

Abstract: Hepatitis C virus-related chronic hepatitis may be associated with various immunological disorders. The aim of this study was to determine prospectively the prevalence of the clinical, biochemical and pathological immunological abnormalities in a series of 61 consecutive patients with chronic hepatitis C, compared with those in 61 age- and sex-matched control subjects without markers of hepatitis C virus and hepatitis B virus infections and with those in 61 patients with chronic hepatitis B. The following inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
258
2
28

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 501 publications
(297 citation statements)
references
References 29 publications
9
258
2
28
Order By: Relevance
“…Among the 12 studies, hypothyroidism was reported in 11 [7,[15][16][17][18][19][20][21][22][23][24], while hyperthyroidism in 5 studies [16,20,21,23,24]. TGAb was covered in 8 studies [7,15,17,18,[20][21][22][23], TPOAb in 6 studies [16,17,[20][21][22][23] and ATMA in 5 studies [6,7,15,19,22].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 12 studies, hypothyroidism was reported in 11 [7,[15][16][17][18][19][20][21][22][23][24], while hyperthyroidism in 5 studies [16,20,21,23,24]. TGAb was covered in 8 studies [7,15,17,18,[20][21][22][23], TPOAb in 6 studies [16,17,[20][21][22][23] and ATMA in 5 studies [6,7,15,19,22].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…TGAb was covered in 8 studies [7,15,17,18,[20][21][22][23], TPOAb in 6 studies [16,17,[20][21][22][23] and ATMA in 5 studies [6,7,15,19,22].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dominant T-cell suppression of B cells producing autoantibodies 24 Autoimmun Highlights (2010) 1: [23][24][25][26][27][28][29][30][31][32][33][34][35] seems to be attenuated. An autoreactive T-cell response may be responsible for endocrine disorders in chronic HCV infection [17].…”
Section: Pathogenesis Of Extrahepatic Manifestationsmentioning
confidence: 99%
“…According to Sene et al [31] cryoglobulinaemic vasculitis is associated with advanced age, longer duration [32]. MC syndrome is characterized by a typical clinical triad: purpura, weakness, arthralgia [33]; the most frequent target organs are skin, joints, nerves and kidneys.…”
Section: Hcv-associated MC Cryoglobulinaemiamentioning
confidence: 99%